Review of Keith Moser, Contemporary French Environmental Thought in the Post-COVID-19 Era (Palgrave Macmillan/Springer Nature, 2022) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2023)
Review of Keith Moser, Contemporary French Environmental Thought in the Post-COVID-19 Era (Palgrave Macmillan/Springer Nature, 2022).